AKUNTABILITAS KINERJA INSTANSI PEMERINTAH PADA PEMERINTAH KABUPATEN PASER - Hendrik Latief; Syachrumsyah Asri; Agus Santosa (Halu Oleo University, 2022)
This study aims to determine the Performance Accountability Of Government Institutions In The Government Of Paser District. This study uses a qualitative approach with a descriptive type and uses interactive data analysis techniques according to Miles Huberman and Saldana (2014). The results of this study indicate that the implementation of public accountability has not gone well, this is because its implementation is still oriented towards fulfilling documents while the quality of the substance of documents has not been touched in depth. This condition is exacerbated by the presence of inhibiting factors in its implementation, namely the lack of commitment at the level of heads of regional apparatuses, lack of communication and coordination in its implementation and the lack of resource support such as a lack of capacity in managing SAKIP human resources, minimal budget and the absence of supporting facilities for an integrated data management management system. . The recommendations are carrying out improvements to planning documents, improving implementation and monitoring and evaluation mechanisms, implementing business process improvements so that they are in line with the strategic plan, optimizing the roles and functions of the local government SAKIP Team and the regional apparatus LKjIP Team.